Efektivitas Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Matematika Kelas I SD Supriyadi 02 Semarang - Afik Kushendrawan; Noor Miyono; Ranto Netty Sofiati (Departement of Mathematics Education, 2024)
Quality education must be supported by the selection of appropriate resources and learning models. The aim of this research is to determine the effectiveness of the Problem Based Learning model in improving Mathematics Learning Outcomes for Class I SD Supriyadi 02 Semarang. This research is quantitative research. The research design used was pre-experimental with a one group pretest posttest design system. The population in this study was 26 students with 14 female students and 12 male students. The sampling technique used was a saturated sample. Data collection techniques use tests. Data analysis techniques include normality tests, homogeneity tests and hypothesis tests. The results obtained were that the pretest score obtained an average score of 59.23 with a posttest score of 80.00. Based on the results of the t-test, the sig (2-tailed) value is 0.000 < 0.05, meaning that H0 is rejected and H1 is accepted. The research results show an increase in learning outcomes through the Problem Based Learning learning model in class I.